The control effect and induced disease resistance mechanism of Bacillus tequilensis on wheat powdery mildew - Qiuyan Bi; Fen Lu; Jie Wu; Xiangyu Liu; Xiuying Han; Jianjiang Zhao (Biological Control)
Blumeria graminis f. sp. Tritici causes wheat powdery mildew (WPM) and severe wheat damage worldwide. To prevent WPM and emerging chemical fungicide resistance, researchers investigated the control effectiveness and induced disease resistance mechanisms of the biocontrol agent Bacillus tequilensis. Its inhibitory effect was determined via an in vitro method combined with microscopic observation, and the control effect was clarified via pot and field verification. Using transcriptome technology, we determined the differences in wheat gene expression in after treatment with B. tequilensis and verified the main molecular mechanism of B. tequilensis-induced resistance. The effects on wheat defence enzymes were clarified via physiological and biochemical techniques. The results revealed that B. tequilensis controlled WPM at an effective concentration of 1 × 107 cfu/mL or higher. The inhibitory effect in vitro was 90.91–100.00 %. The potted control effect was 92.98–100.00 %. The field control effect was 83.21–100.00 %. Transcriptome sequencing analysis revealed 1,472 significantly upregulated genes and 1,995 downregulated genes. The differentially expressed genes were enriched in several pathways related to amino acid biosynthesis and metabolism. The expression levels of actin-7-like, lipoxygenase, linoleic acid 9S-lipoxygenase 6-like, pathogenesis-related protein PR-1-like, superoxide dismutase, phenylalanine ammonia lyase and polyphenol oxidase were significantly increased. The relative enzymic activities induced by B. tequilensis presented maximum differences between 2.63-fold and 3.43-fold. Our results suggest that B. tequilensis combats WPM by inducing systemic acquired resistance in wheat, helps elucidate biological agent targeted control mechanisms and provides a foundation for field application.